Development of Measurement Tool for Understanding, Application, and Reasoning Mathematics of Madrasah Ibtidaiyah Students - Ismail, Ilyas; Nursalam, Nursalam; Angriani, Andi Dian; Kusumayanti, Andi (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
This study aims to develop a measurement tool for students' understanding, application and mathematical reasoning ability at Madrasah Ibtidaiyah in South Sulawesi. This research is a formative research type of Research and Development (R&D) research through 4 (four) stages, namely: the preliminary stage; the stage of self evaluation (curriculum analysis, material, students) and design; prototyping stage (validation, evaluation and revision) which includes expert reviews, one-to-one and small groups; and the feld test stage. The product of this research was an assessment instrument in the form of questions that measured the ability of understanding, application, and mathematical reasoning of Madrasah Ibtidaiyah students. The test subjects in this study were fourth grade MI students in Makassar City, Gowa regency, and Sinjai regency. The results of the content validity based on the rater indicated that the test items needed were declared valid after being assessed by the rater and analyzed using the CVR (Content Validity Ratio) and CVI (Content Validity Index). In the reliability test, the results of the analysis conducted for multiple choice questions and the contents were in the category of "high" which means that the measurement tools for comprehension, application, and reasoning were indicated to be reliable.Penelitian ini bertujuan untuk mengembangkan alat ukur kemampuan pemahaman, apÃ‚Âlikasi, dan penalaran matematika siswa pada Madrasah Ibtidaiyah di Sulawesi Selatan. Penelitian ini merupakan jenis penelitian Research and Development (R & D) tipe formative reÃ‚Âsearch melalui 4 (empat) tahap yaitu: tahap preliminary; tahap self evaluation (analisis kurikuÃ‚Âlum, materi, siswa) dan design; tahap prototyping (validasi, evaluasi dan revisi) yang meliÃ‚Âputi expert reviews, one-to-one dan small group; dan tahap feld test (uji coba lapangan). Produk penelitian ini adalah instrument penilaian berupa soal-soal yang akan mengukur kemamÃ‚Âpuan pemahaman, aplikasi, dan penalaran matematika siswa Madrasah Ibtidaiyah. Subjek uji coba pada penelitian ini adalah siswa kelas IV MI di Kota Makassar, Kab. Gowa, dan Kab. Sinjai. Hasil validitas isi (Content validity) berdasarkan rater menunjukkan bahwa butir-butir tes yang dibut dinyatakan valid setelah dinilai oleh rater dan dianalisis dengan menggunakan CVR (Content Validity Rasio) dan CVI (Content Validity Indeks). Pada uji reliabiliÃ‚Âtas, alat ukur kemampuan pemahaman, aplikasi, dan penalaran dikatakan reliabel.